Aloe Vera Juice Decrease The Amount Of Blood Glucose Level In Patient With Diabetic Type Ii - Kusnanto Kusnanto; Sriyono Sriyono; Dian Eko Puji Astuti (Jurnal Ners, 2008)
Introduction: Aloe vera is a tropical plant that known can decrease the amount of blood glucose level in patient with diabetic type II. Diabetes mellitus is a disease cause by an increasing amount of blood glucose level that is reduce by conditions of the insulin. The aimed of this study was to analyze the effect of Aloe vera administering on decreasing blood glucose level for Diabetes mellitus type II patient.Methods: A quasy experimental non randomized control group pre post test design was used in this study. There were 20 respondents divided into 3 group of treatment. Each group is given 100 gr/day 200 gr/day and 300 gr/day Aloe vera juice respectively. Data were collected by using observation and analyzed by using One way Anova and Paired t-Test with significance level α≤ 0.005.Results: The result showed that Aloe vera juice administering can decrease blood glucose level, with 100 gr/day, 200 gr/day, 300 gr/day (p=0.000). Conclusion: It can be proven that Aloe vera juice administering can decrease blood glucose level, it’s because the content of Aloe vera more complete and effect from alprogen which impede absorption glucose and blood glucose level. Further study are recommended to measure the effect of Aloe vera juice on blood glucose level with more consider on gender, age, total calorie consumption, obesity, activities, and stress.